2022
DOI: 10.3390/ijerph19074260
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Response to Anthracyclines in Ovarian Cancer

Abstract: (1) Background: Anthracyclines are intriguing drugs, representing one of the cornerstones of both first and subsequent-lines of chemotherapy in ovarian cancer (OC). Their efficacy and mechanisms of action are related to the hot topics of OC clinical research, such as BRCA status and immunotherapy. Prediction of response to anthracyclines is challenging and no markers can predict certain therapeutic success. The current narrative review provides a summary of the clinical and biological mechanisms involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…The PFI correlates with the efficacy of subsequent therapy for platinum-refractory or platinum-resistant ovarian cancer [52] . The PFI helps guide individualized treatment to optimize the survival benefit for OC patients according to guidelines [53] . In our study, we found that the CDC7 inhibitor XL413 delayed tumor recurrence after carboplatin treatment, which means that this new combination therapy may prolong the PFI, thus creating an opportunity for platinum-based chemotherapy for recurrent OC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The PFI correlates with the efficacy of subsequent therapy for platinum-refractory or platinum-resistant ovarian cancer [52] . The PFI helps guide individualized treatment to optimize the survival benefit for OC patients according to guidelines [53] . In our study, we found that the CDC7 inhibitor XL413 delayed tumor recurrence after carboplatin treatment, which means that this new combination therapy may prolong the PFI, thus creating an opportunity for platinum-based chemotherapy for recurrent OC patients.…”
Section: Discussionmentioning
confidence: 99%